Willy's Wonderland [videorecording (DVD)] - Lewis, Kevin (Director); Cage, Nicolas, 1965-; Cage, Nicolas, 1965-; Tosta, Emily; Grant, Beth, 1949- (Screen Media Films, 2021)
A drifter is bamboozled into a janitorial job at Willy's Wonderland, a condemned amusement park.